2018
DOI: 10.1167/18.3.17
|View full text |Cite
|
Sign up to set email alerts
|

Ensemble representation for multiple facial expressions: Evidence for a capacity limited perceptual process

Abstract: We tested the processing capacity of establishing ensemble representation for multiple facial expressions using the simultaneous-sequential paradigm. Each set consisted of 16 faces conveying a variable amount of happy and angry expressions. Participants judged on a continuous scale the perceived average emotion from each face set (Experiment 1). In the simultaneous condition, the 16 faces were presented concurrently; in the sequential condition, two sets, each containing eight faces, were presented successivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 78 publications
(111 reference statements)
0
16
0
Order By: Relevance
“…Furthermore, stimulus variance in a set affected the number of faces involved in ensemble coding ( Ji et al, 2020 ). Ji et al ( 2018 , 2020 ) provided direct evidence suggesting that stimulus variance in a set could affect ensemble coding. The extraction of a mean representation is a capacity-limited perceptual process ( Ji et al, 2018 ), and stimulus variance in a set might be an important factor causing different relationships between the mean representation and individual representations in different studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, stimulus variance in a set affected the number of faces involved in ensemble coding ( Ji et al, 2020 ). Ji et al ( 2018 , 2020 ) provided direct evidence suggesting that stimulus variance in a set could affect ensemble coding. The extraction of a mean representation is a capacity-limited perceptual process ( Ji et al, 2018 ), and stimulus variance in a set might be an important factor causing different relationships between the mean representation and individual representations in different studies.…”
Section: Discussionmentioning
confidence: 99%
“… Ji et al ( 2018 , 2020 ) provided direct evidence suggesting that stimulus variance in a set could affect ensemble coding. The extraction of a mean representation is a capacity-limited perceptual process ( Ji et al, 2018 ), and stimulus variance in a set might be an important factor causing different relationships between the mean representation and individual representations in different studies. Although the present study controlled the stimulus variance in a set, we did not investigate the effect of stimulus variance on the processing of the mean emotion representation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with the view that face ensemble characteristics cannot be computed in the absence of encoding individual faces, a recent study by Neumann et al (2018) showed that manipulations that reduced the fidelity of encoding of individual faces also reduced the precision of encoding ensemble characteristics (in this case, mean identity). There is considerable evidence from other studies, however, that SSRs can be computed for emotional expressions (Haberman & Whitney, 2007, 2010; Ji, Chen, Loeys, & Pourtois, 2018; Li et al, 2016; Sun & Chong, 2020) suggesting that information about second-order relations in facial features can be aggregated across multiple faces concurrently. The face inversion effect provides an interesting potential answer to this question.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, one could wonder how many faces in a set, if not all, contribute to the perception of that crowd's mean emotion. This question is reminiscent of a current debate in the literature about the actual meaning and function of ensemble representations, and more specifically whether they offer a means to surpass traditional bottlenecks in information processing and attention selection (Alvarez, 2011;Chong & Treisman, 2005;Cohen et al, 2016;Attarha, Moore, & Vecera, 2014;Ji, Chen, Loeys, & Pourtois, 2018). If sampling only 3-4 items (this size being traditionally assumed to correspond to the upper bound for attention capacity; see Pylyshyn & Storm, 1998) or even fewer items in a set could adequately explain human observers' performance when many more items are shown in the visual field, then the claim that ensemble representations are capacity unlimited or can overcome the bottlenecks in visual perception might need to be reconsidered.…”
Section: Introductionmentioning
confidence: 99%